Nanoporous carbon as a sensing platform for DNA detection : the use of impedance spectroscopy for hairpin-DNA based assay - Poh, Hwee Ling (2013)
Nanoporous carbons represent well defined materials with large surface area, defined porosity, high electrical conductivity and fast heterogeneous electron transfer rates. These materials are seldom used for sensing and even more rarely for biosensing. We for the first time show the application of nanoporous carbon using electrochemical impedance spectroscopy technique to detect DNA hybridization and polymorphism. Our findings demonstrated the proof of concept of using nanoporous carbon in nucleic acid analysis, being able to detect the presence of a single nucleotide polymorphism.